Genetic Analysis of EGLN1 C127S Variant in Taiwanese Parkinson's Disease. (25th April 2020) - Chiang, Han-Lin; Chen, Chiung Mei; Chen, Yi-Chun; Chao, Chih-Ying; Wu, Yih-Ru; Lee-Chen, Guey-Jen
Abstract : Parkinson's disease (PD) is a neurodegenerative disorder related to nigrostriatal dopaminergic neuron degeneration and iron accumulation. As a cellular oxygen sensor, prolyl hydroxylase domain containing protein 2 (PHD2, encoded by egl-9 family hypoxia inducible factor 1, EGLN1 ) modifies hypoxia-inducible factor alpha (HIF- α ) protein for proteasomal destruction under normoxic condition. In addition, 2-oxoglutarate- (OG-) dependent dioxygenase activity of PHD2 is involved in the oxygen and iron regulation of iron-responsive element binding protein 2 (IRP2) stability. Previously increased expression of EGLN1 was found in the substantia nigra of the parkinsonian brain. We investigated the possible role of c.380 G > C (p.C127S) of EGLN1 gene in Taiwanese patients with PD. 479 patients and 435 healthy controls were recruited. Polymerase chain reaction and Bsm AI restriction enzyme analysis were applied for analysis. An association between CC genotype and reduced PD risk in the recessive model (CC vs. GG + GC) was found. Our study provides a link between EGLN1 c.380 G > C SNP and the development of PD.